EFFECTS OF MUTANT DROSOPHILA K(+) CHANNEL SUBUNITS ON HABITUATION OF THE OLFACTORY JUMP RESPONSE - JOINER, M. A. (2007)
The olfactory-jump response assay was used to analyze habituation in Drosophila mutants of potassium (K(+)) channel subunits. As with physiological assays of the giant fiber-mediated escape reflex, mutations at loci that encode K(+) channel subunits have distinct effects on habituating the olfactory-jump response. The data for slowpoke and ether à go-go indicate similar effects on habituation of the olfactory-jump response and the giant fiber-mediated escape. Habituation in the olfactory jump assay in Hyperkinetic and Shaker mutants was drastically different from the degree of defect in the giant fiber-mediated escape reflex, indicating differential control mechanisms underlying the two forms of non-associative conditioning.